The effect of using metacognitive thinking in understanding moral concepts among eighth grade students in Jordan - Radwan, Manal Mohamed (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the effect of using metacognitive thinking in understanding moral concepts among eighth grade students in Jordan. The researcher used the quasi-experimental approach to identify the effect of using metacognitive thinking in developing the comprehension of ethical concepts. The researcher prepared a test to measure the moral concepts of the study sample, which consisted of (72) students in two groups (control – experimental). The study reached several results, the most important of which is the existence of an effect of the metacognitive thinking strategy in developing the comprehension of moral concepts for the tenth grade students, where the experimental sample students outperformed the control sample students. The study recommended the necessity of using the metacognitive teaching strategy in all other units of Islamic education, as a unit (creed, interpretation, hadith.
Keywords: Islamic education; metacognitive thinking; Understand ethical concepts